Neonatal Outcomes of Small for Gestational Age Preterm Infants in Canada - Qiu, Xiangming; Lodha, Abhay; Shah, Prakesh S.; Sankaran, K.; Seshia, Mary M.K.; Yee, Wendy; Jefferies, Ann; Lee, Shoo K.; null (American Journal of Perinatology, 2012)
To compare the effect of small for gestational age (SGA) on mortality, major morbidity and resource utilization among singleton very preterm infants (<33 weeks gestation) admitted to neonatal intensive care units (NICUs) across Canada. Infants admitted to participating NICUs from 2003 to 2008 were divided into SGA (defined as birth weight <10th percentile for gestational age and sex) and non-small gestational age (non-SGA) groups. The risk-adjusted effects of SGA on neonatal outcomes and resource utilization were examined using multivariable analyses. SGA infants (n = 1249 from a cohort of 11,909) had a higher odds of mortality (adjusted odds ratio [AOR] 2.46; 95% confidence interval [CI], 1.93–3.14), necrotizing enterocolitis (AOR 1.57; 95% CI, 1.22–2.03), bronchopulmonary dysplasia (AOR 1.78; 95% CI, 1.48–2.13), and severe retinopathy of prematurity (AOR 2.34; 95% CI, 1.71–3.19). These infants also had lower odds of survival free of major morbidity (AOR 0.50; 95% CI, 0.43–0.58) and respiratory distress syndrome (AOR 0.79; 95% CI, 0.68–0.93). In addition, SGA infants had a more prolonged stay in the NICU, and longer use of ventilation continuous positive airway pressure, and supplemental oxygen (p < 0.01 for all). SGA infants had a higher risk of mortality, major morbidities, and higher resource utilization compared with non-SGA infants.
Keywords: small for gestational age; very preterm; neonatal intensive care unit; neonatal outcomes